Fleksibilitas Pemaknaan Wakaf Tunai di Indonesia: Studi terhadap Lembaga Filantropi dan Lembaga Keuangan - Hilman Latief; Syarif As'ad; Miftakhul Khasanah (Fakultas Studi Islam dan Peradaban, Universitas Muhammadiyah Yogyakarta, 2015)
This paper discusses cash waqf innovation in Indonesia by exploring the experience of Islamic financial institutions and Islamic philanthropy organizations . The increase of opportunity to gain public fund from the Muslim middle-class has lead to the dynamics and inovatove waqf (endowment) management. This article focuses on the socio-economi context that fueled the incease of cash waqf practice, and various innovative forms of Islamic phinathropy. This paper argues that the concept of cash waqf has been translated in various ways, and there have been different forms of cash waqf management. This suggests that people put much attention to ideas of maslahat (the benefit of society) in practicing cash waqf instead of simply rigidly following Islamic jurisprudential rule or positive law